Measuring Positive Aging in the elderly - Mohamed Hassan, Ayaat; Ali Hussein, Thuriayh (Al-Adab Journal, 2021)
The current research targeted a positive aging measurement of older aging is recognized for older age in accordance within the role of the elderly. The current research sample (286) of the elderly in Baghdad province has reached the random way. Search tool: The positive aging scale of Lars (2005) was built. Then the measurement will be extracted. The results of the research showed: The elderly have positive aging and statistically significant, and the presence of significant differences in favor of males outside and inside the Houses.